P072 Non-invasive Vagal Nerve Stimulation to Treat Crohn Disease and Ulcerative Colitis in Children and Young Adults: A Proof-of-Concept Clinical Trial - Sahn, Benjamin; Pascuma, Kristine; Tracey, Kevin; Markowitz, James (The American journal of gastroenterology, 2021)
Current inflammatory bowel disease (IBD) therapies are limited by incomplete efficacy, loss of response, side effects and high costs. Vagal nerve stimulation (VNS) is an investigational Bioelectronic Medicine therapy targeting the nervous system to treat IBD through an 'inflammatory reflex' that reduces systemic inflammation. Data in humans with IBD are promising but limited to two small studies using a cervically implanted VNS device in adults with Crohn disease (CD); no data exist to date using a non-invasive VNS modality in IBD. This study aimed to evaluate the efficacy and safety of transcutaneous auricular VNS (ta-VNS) in children and young adults with CD or ulcerative colitis (UC). IBD patients 10-21 years of age with mild/moderate CD or UC who did not achieve remission with conventional therapy, and a fecal calprotectin (FC) >200 ug/g within 4 weeks of study entry were enrolled. Subjects were randomized to receive either ta-VNS using a transcutaneous electrical nerve stimulator unit targeting the cymba conchae of the external left ear, or sham stimulation of the posterior lower leg, for 5 minutes once daily for a 2-week duration followed by a switch to the alternative stimulation for an additional 2 weeks. At week 4, all subjects were assigned to receive active ta-VNS for 5 minutes twice daily until week 16 so that all received 14 weeks of active ta-VNS by the end of the study. Primary study endpoint was defined as ∆FC ≥50% reduction from baseline to week 16. Secondary endpoints included improvement in weighted Pediatric Crohn Disease Activity Index (wPCDAI) or Pediatric Ulcerative Colitis Activity Index (PUCAI). Twenty-two subjects were enrolled (12 UC, 10 CD; median age 14.4 years [range 10-21] 54.5% male). Median baseline FC was 587 (range 18 - 3828, SD 1074). 5 subjects (4 UC, 1 CD) had FC levels 12.5 at baseline, 3 (50%) achieved clinical remission (wPCDAI ≤ 10) at week 16. In the full UC cohort (n = 12), baseline PUCAI ranged from 0-45. In the 6 with PUCAI > 10 at baseline, 2 (33%) achieved clinical remission at week 16. There were no safety concerns. Non-invasive ta-VNS reduced FC levels and improved symptoms in a pediatric cohort with mild/moderate IBD. Further research is needed to identify optimal electrical dose and settings to achieve peak anti-inflammatory effect and to identify the mechanistic principles for this therapy.